Group-Oriented Nature of Traditional Igbo Counselling System - Iroaga, Nwab; Ugorji, Rex (Canadian Journal of Counselling and Psychotherapy, 2012)
The authors identify and discuss the major beliefs and prac- tices underlying Igbo traditional counselling systems. They point out the absence of professional counsellors, but emphasize Igbo concern for human life in relationship with others. The group-oriented nature of Igbo tradi- tional counselling practices are described by examining counselling pro- cesses within four cultural sub-system: the family, intimacy groups, the age-group, and the delegated group. In the organizational diversity and complexity of Igbo village groups, certain types of social forms and processes occur frequently and are fea- tures which provide cohesion and order to Igbo society. Much of these center around unique group counselling practices that occur at many different levels in the society. This paper outlines the major beliefs and practices underlying Igbo traditional counselling systems. Counselling and psychotherapy have been used to apply to inter- actions where one person, referred to as the counsellor or the therapist, has taken the responsibility for making his role in the interaction process contribute positively to the other person's personality development. For purposes of simplicity in this paper, "Counselling" will refer to the helping and therapeutic practices within the group sys- tems described below. These will include interactive influences at work, skills and knowledge employed, and personality reorganizations and experiencing that result — in short, how problems of living are minimized.